Percentage Area Reduction of Uncut Fibre of Drilling Pineapple Leaf Fibres Reinforced Composites with Peck Drilling Canned Cycle Method - Mulyadi, Ismet Hari; Rusdi, M.F.R.; Kurniawati, Loli; Ma'sum, Arif (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
The effectiveness of utilizing the peck drilling canned cycle to minimize hole delamination has been demonstrated. However, its potential to reduce uncut fiber resulting from fiber fracture and pull-out has not been fully recognized, particularly in drilling natural fiber-reinforced polymer composites. Therefore, this study investigated the performance of this established method and compared it with the conventional drilling approach using a stepped geometry drill bit, which is purported to minimize hole delamination and, consequently, reduce uncut fiber. A series of hole-making processes were carried out according to a Completely Randomized Design (CRD) experimental plan. Different feed movements were employed to elicit responses, specifically the extent of uncut fiber area. The findings indicate that employing the established method could reduce uncut fibers by approximately 18.6%, representing a 2% enhancement compared to the alternative approach. Hence, the peck drilling canned cycle strategy offers a promising and cost-effective alternative to using specialized drill bits or high-performance cutting tools.